Faktor–Faktor yang Memengaruhi Optimalisasi Penangkapan Ikan dengan Metode Transformasi Box Cox pada Regresi Linier Berganda - Fuji Rahayu Wilujeng (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
In general, the ratio of the ocean and land area on this earth is 70 to 30. Many potentials of water can be used to promote human well-being. Even today, many developed countries from all over the world are competing to advance their maritime activities and their auspices for the country's interests so that the role of the sea becomes dominant for developing of the countries. One of the most common marine activities people do is sea fishing. the marine and fisheries sector has enormous potential to become a national economist. In Indonesia, many people depend on the fisheries sector. So, in this research that will be discussed is to determine the model of the number of marine fish production in East Java Province with Box-Cox Transformation method on Multiple Linear Regression to get significant control variable on the amount of sea fish production in East Java Province. The result of regression using Box-Cox transform shows that some variables such as the number of fishermen, fishing equipment, and boat or fishing boat motor have a significant influence on R2 89.3%. With this model, it is hoped to be one strategy to increase the number of fishing through the selection of appropriate control variables.